Hubungan Pengetahuan Dan Sikap Ibu Tentang Gizi Balita Dengan Status Gizi Balita Diwilayah Kerja Puskesmas Hanura Kecamatan Teluk Pandan Kabupaten Pesawaran Tahun 2024 - Cut, Cut Fitria Febriana; Adyas, Atikah (Universitas Prima Indonesia, 2024)
Nutritional problems are disorders of the health and well-being of an individual, group or community as a result of an imbalance between intake and the body's need for food and the influence of disease interactions (infections). Beside that, the mother's knowledge and attitude can affect intaking for children. Pesawaran is a Regency in Lampung that has nutritional problems. Based on the results of the 2018 Riskesdas of Lampung Province, it is known that the prevalence of nutritional status (W/A) toddlers aged 0-59 months is 3.13% malnutrition, 12.81% undernutrition, 81.22% good nutrition, and 2.83% overnutrition. While the prevalence of nutritional status (W/H) is very thin 3.89%, thin 6.75%, normal 82.18%, and obese 7.18%. While the prevalence of nutritional status (W/H) in Pesawaran Regency is very thin 2.97%, thin 10.33%, normal 82.50%, obese 4.20%. The prevalence of nutritional status (W/A) of malnutrition was 3.79%, undernutrition 17.51%, good nutrition 78.15% and overnutrition 0.55%. The research used quantitative descriptive with data collection method through Cross Sectional design. The total population of all mothers who have toddlers aged 12-60 months at the Desa Hurun Posyandu was 169 with a total 119 samples. The sampling technique used random sampling, data collection using questionnaires, data analysis using Univariate and Bivariate (Chi square test). The results of the study showed from 119 there were 31 respondents (100%) who had a good level of knowledge, there were 72 respondents (100%) who had sufficient knowledge and there were 16 respondents (100%) who had insufficient knowledge. Meanwhile, the results of the mother's attitude showed from 119 respondents had 21 respondents (100%) a good attitude, 1 responden (1,3%) who have a less positive attitude 83 respondents (98,7%) had a sufficient attitude, and 15 respondents (100%) had a poor attitude. The results of the study showed that there was a significant relationship between mother's knowledge and the nutritional status of toddlers with a p-value of 0.000 (p <0.05) and there was a significant relationship between mother's attitude and the nutritional status of toddlers with a p-value of 0.000 (p <0.05). Based on these results, it can be concluded that there is a significant relationship between mother's knowledge and attitude about toddler nutrition and the nutritional status of toddlers in the Hanura Puskesmas area. Keywords: Mother's Knowledge, Mother's Attitude, Toddler Nutritio